Learning Strategies for Islamic Religious Education Based on the Values of Piil Pesenggiri to Enhance Religious Moderation - M.Makhrus Ali; Meilisa Sajdah; Khairunesa Isa; Dwi Noviatul Zahra; Tri Haryati; Suriyah Suriyah; Winarko Winarko (Universitas Nurul Jadid, 2025)
This study aims to analyze Islamic Religious Education learning strategies based on the values of Piil Pesenggiri in enhancing religious moderation at STAI Ibnu Rusyd Kotabumi, North Lampung. This research is motivated by the importance of strengthening religious moderation amid the growing issues of intolerance, radicalism, and the weakening of local cultural values among the younger generation. The study employed a qualitative approach with a case study design. Data collection techniques were conducted through observation, in-depth interviews, and documentation. The research informants consisted of Islamic Religious Education lecturers, students, and campus authorities selected using purposive sampling techniques. Data analysis used the Miles and Huberman model through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source triangulation, method triangulation, and member checking. The results of the study indicate that Piil Pesenggiri has strong relevance to the principles of religious moderation because it contains values of self-respect, social tolerance, openness, solidarity, and harmonious living. The internalization of Piil Pesenggiri values was carried out through learning activities, academic culture, lecturers’ role modeling, and students’ social activities. Local wisdom-based learning strategies were implemented through planning, implementation, academic culture management, and learning evaluation oriented toward shaping students’ moderate character. This study confirms that Piil Pesenggiri is not only a cultural identity of the Lampung community but can also serve as a pedagogical foundation and a management strategy in Islamic education to strengthen religious moderation in Islamic higher education institutions